Diuretics and advanced features of nephroprotection - Ivanov, D.D.; Rostaing, Lionel (KIDNEYS, 2021)
The most frequently used diuretics in nephrology, and the scheme and dosages used for their prescription are considered. Attention is focused on a new class of hypoglycemic drugs (gliflozins) that can provide nephroprotection to patients with diabetic nephropathy, and probably those with chronic kidney disease without diabetes mellitus type 2.